Números construtíveis e uma proposta de seu ensino para o novo ensino médio - Queiroz Neto, Gregório Pereira de (2023)
This work presents an introduction to the theory of bodies with emphasis on extensions of elds and also approaches polynomials in an introductory way. we present yet the theory of constructible numbers using only unmarked ruler and compass. Finally, the application proposal is presented.